The Phenomenon of Unregistered Marriages Due to Rejection of Marriage Dispensation: Study of the Enrekang Religious Court and KUA Kec. Baroque - Abd Gaffar; Agus Muchsin; Fikri; Rusdaya Basri; Zainal Said (Universitas Muhammadiyah Palu, 2025)
The general aim of this research is to find out the reality/phenomenon of unregistered marriages in the district. Baroko, To find out the judge's considerations in rejecting requests for marriage dispensation at the Religious Court and KUA District Determination. Baroko, and to find out legal responsibility for marriage dispensations in Kec. Baroque. This type of research is qualitative research carried out at the Enrekang Religious Court and KUA District. Baroque. The main instruments of this research are observation, interviews and documentation. Data sources are primary data and secondary data. The research results show that first; The reality/phenomenon of marriage is not recorded in Kec. Baroko, namely unregistered marriages in Baroko District, illustrates a complex social phenomenon, where a number of couples choose not to officially register their marriages. This phenomenon reflects various factors, ranging from a lack of understanding of the importance of marriage registration, administrative obstacles, to economic and social factors that influence individual decisions. The consequences of unregistered marriages can impact the legal rights of spouses and their children, as well as hinder access to public services and legal protection, secondly; The judge's consideration in rejecting the application for marriage dispensation in the Religious Court and KUA District Determination. Baroko, namely the judge's considerations in rejecting requests for marriage dispensation at the Religious Court and KUA District. Baroko is based on the insufficiency of legal reasons, evidence, and fulfillment of the requirements stipulated by law. The judge assesses whether the application meets the best interests of the child and is in accordance with applicable legal norms, and thirdly; Legal responsibility for marriage dispensation in Kec. Baroko, namely legal responsibility for marriage dispensation in Baroko District includes the obligation to comply with legal requirements stipulated by statutory regulations. Marriage dispensation must be carried out on the basis of strong reasons and compliance with correct administrative procedures. Failure to comply with these provisions can have legal consequences for the parties involved, including protecting children's rights and enforcing legal norms.